Insect traces on Lower Gondwana plants of Ib River Basin, Odisha: First record from Late Permian sediments of India. Issue 6 (14th March 2022) - Tripathy, Geetika; Goswami, Shreerup
ABSTRACT: The Ib River Basin, located in the south‐eastern part of the Son‐Mahanadi Master Basin, is renowned for its reserve of well‐diversified Lower Gondwana plant megafossils. The remains of Glossopteris flora collected from a Late Permian Gondwana (Lower Kamthi Formation) exposure, near Himgir Village, Ib River Basin, Odisha, has demonstrated a record of different types of insect traces. The structures are compatible with a variety of insect activities on fossil leaves. Different feeding traces such as leaf margin and surface feeding traces, cuspate margin feeding traces, obliterated surfaces and blotch marks are found in the Glossopteris leaves. Egg pouches found along the midrib and on the lamina in the Glossopteris leaves are the traces of egg‐laying. The various traces of insect activities recorded in the present investigation reveal the survival of a diverse insect fauna during the Late Permian Glossopteris flora of India. It is the first report of its kind in the Mahanadi Gondwana Master Basin of India, and also it is the first record of insect traces in the Late Permian sediments of India. Abstract : Different insect feeding traces, traces of their egg laying and blotch marks are found in the Glossopteris leaves recorded from Ib River Basin, Odisha. It is the first report of insect traces in the Late Permian sediments of India.